Nietzsche's Animal Philosophy : Culture, Politics, and the Animality of the Human Being - Miller, David Lee, 1951-; Levine, Nina S., 1950- (Book collections on Project MUSE., 2009)
Harry Berger, Jr., has long been one of our most revered and respected literary and cultural critics. Since the late nineties, a stream of remarkable and innovative publications have shown how very broad his interests are, moving from Shakespeare to baroque painting, to Plato, to theories of early culture. In this volume a distinguished group of scholars gathers to celebrate the work of Harry Berger, Jr. To "celebrate," in Berger's words, is "to visit something either in great numbers or else frequently-to go away and come back, go away and come back, go away and come back. Celeb.